Reporting Intellectual Capital in Annual Reports: Evidence from Indonesia - Sihotang, Parulian; Sanjaya, Yulia (UI Scholars Hub, 2009)
This exploratory study which replicates the content analysis methodology of Guthrie et all (1999, 2004) towards Intellectual Capital (IC) disclosures in the annual report has set several objectives. Primarily, the empirical investigation assesses the extent to which Indonesian listed companies are publicly reporting their IC both the amount and type of information being reported. Secondly, the investigation also examines the extent to which the various categories of IC are represented in the annual reports of the sample companies. Finally, the study explores the extent to which the level of IC disclosures could be related to companies' characteristics such as industry category, age, ownership structure and market capitalization. The sample was Indonesia's 23 largest companies listed in the Jakarta Stock Exchange. In light of research limitations, the preliminary and tentative indings of this study indicate that irst of all, similar to indings worldwide, Indonesian companies have substantial intellectual capital and they do aware and disclose their intellectual capital in the annual reports. Secondly, IC that tends to be most often reported is relational capital, followed by human capital and organizational capital. Thirdly, even though the trend in IC disclosure as a whole is generally increasing, there is no conclusive and predictable pattern found. Fourthly, the IC identiied and reported is inconsistent as no framework available in helping the companies discloses intellectual capital. Fifthly, most of the intellectual capital components identiied are in qualitative format. Sixthly, even though the study did not ind a conclusive evidence regarding the relationship between the level of IC disclosure and company characteristics such as industry, age, ownership structure, and market capitalization, however some indings are noteworthy. Finally, a comprehensive framework is yet to be developed, especially for collecting and reporting IC formation for consistency and comparability purposes.